Multiple keratin granulomata: A potential histologic clue to cutaneous squamous cell carcinoma responding to programmed cell death protein 1 inhibitor therapy. (4th April 2019) - Kahn, Benjamin J.; Parker, Douglas; Yushak, Melinda; Stoff, Benjamin; Blalock, Travis W.
Abstract : We present histologic features of a locally advanced cutaneous squamous cell carcinoma (cSCC) treated with the programmed cell death protein‐1 (PD‐1) antagonist, pembrolizumab, with a partial response. This contributes to a growing body of literature supporting the efficacy of pembrolizumab in treatment of surgically unresectable cSCC. We also provide a detailed description of the histologic features, particularly keratin granulomata with adjacent lymphocytic aggregates and fibrosis, observed in cSCC under treatment with a PD‐1 antagonist.